Fluorescence guided PDT for optimization of the outcome of skin cancer treatment - Blanco, Kate C.; Moriyama, Lilian T.; Inada, Natalia M.; Sálvio, Ana G.; Menezes, Priscila F. C.; Leite, Everson J. S.; Kurachi, Cristina; Bagnato, Vanderlei S. (Frontiers in Physics, 2015)
The photodynamic therapy (PDT) is an alternative technique that can be used for treating superficial basal cell carcinoma (sBCC), Bowen's disease and actinic keratosis with highefficiency. The objective of this study is to present a method where fluorescence imaging together with for PDT as a monitoring guidance in real time. Confirming that the lesion is well prepared and the photosensitizer shows a homogenous distribution, the outcome after few PDT sessions will be more predictable and the recurrence is minimized. Our proposition in this study is use the widefield fluorescence imaging to evaluate the PDT protocol in situ and in real time for each lesion. This evaluation procedure is performed in two steps: first with the monitoring of the production of protoporphyrin IX (PpIX) induced by methyl aminolevulinate (MAL), a derivative of 5-aminolevulinic acid (ALA) and second with the detection of PpIX photobleaching after illumination. The fluorescence images provide information correlated with distinct clinical features and with the treatment outcome. Eight BCC lesions are presented and discussed in this study. Different fluorescence patterns of PpIX production and photobleaching could be correlated with the treatment response. The presented results show the potential of using widefield fluorescence imaging as a guidance tool to customized PDT. This procedure is being incorporated to the main PDT skin cancer protocol applied in Brazil with an excellent outcome.